ANALISIS ALGORITMA C4.5 UNTUK MENENTUKAN TINGKAT PROFIT USAHA PADA PT MEGACIPTA SEJATI - Harina, Harina; Harman, Rika (Computer Science and Industrial Engineering, 2020)
The development of boarding houses in Batam from year to year shows a significant increase. Many people come from distant cities and many people leave their hometowns to come and look for work in Batam, so they do not have a place to live. Many companies are looking for workers to provide housing facilities such as dormitories for workers. PT Megacipta Sejati is a company engaged in the rental of dormitory to companies that provide housing facilities such as dormitories for their workers. During this time the company has a set of data related to the achievement of company performance which has cost a lot but the data cannot be utilized properly. Through the application of data mining technology, a collection of untapped data will be processed and produce new knowledge that becomes valuable and useful for companies, especially in increasing profits. Based on these problems, I as a researcher are interested in researching the c4.5 algorithm analysis to determine the level of business profit at PT Megacipta Sejati. Data Mining is mining or finding new information by looking for certain patterns or rules from a large amount of data that is expected to overcome these conditions. Data Mining itself has several techniques, one of which is classification. The classification technique consists of several methods, and the decision tree is part of the classification method. Then the decision tree method has an algorithm, C4.5 algorithm is one of the algorithms that has a decision tree. The results of this study will produce rules for the company's profit and loss decisions.